Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1097/01.mib.0000437500.60546.2a
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Monitoring of Medication Adherence in a 1-year Clinical Study of 2 Dosing Regimens of Mesalazine for Adults in Remission with Ulcerative Colitis

Abstract: Simple dosing regimens are preferable to multiple daily dosing regimens. Electronic monitoring of adherence should be used more often in clinical studies. Self-reported adherence and tablet counts may underestimate adherence. Adherence declined over time, and adherence was generally lower and more varied for those allocated to the three times daily regimen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(39 citation statements)
references
References 31 publications
2
35
2
Order By: Relevance
“…Of note, when a continuous outcome was used, a correlation approach was considered in 36 comparisons to assess agreement between measurement methods leading to an average correlation of 0.35, ranging from À0.67 to 0.76 [5,8,16,19,24,29,33,34,41,43,55,62,63,65,67,69,86,88,90,91]. For 31 of those correlations, the null hypothesis of no correlation was formally tested and rejected (P < 0.05) in 24 cases (77%) leading to the conclusion that there is a significant linear association between the measurement methods.…”
Section: Analysis Of Extracted Datamentioning
confidence: 99%
“…Of note, when a continuous outcome was used, a correlation approach was considered in 36 comparisons to assess agreement between measurement methods leading to an average correlation of 0.35, ranging from À0.67 to 0.76 [5,8,16,19,24,29,33,34,41,43,55,62,63,65,67,69,86,88,90,91]. For 31 of those correlations, the null hypothesis of no correlation was formally tested and rejected (P < 0.05) in 24 cases (77%) leading to the conclusion that there is a significant linear association between the measurement methods.…”
Section: Analysis Of Extracted Datamentioning
confidence: 99%
“…This substudy demonstrated that adherence to study medication was generally lower and more varied for participants allocated to the TDS regimen. However, as this type of measure was not used for all trial participants, it will not be considered further in this paper [16]. …”
Section: Methodsmentioning
confidence: 99%
“…Tablet count was defined as the number of tablets taken (not present in the container) expressed as the percentage of the correct number of tablets advised by the physician for the study period, that is, 90 tablets. 24 , 25 …”
Section: Methodsmentioning
confidence: 99%